Implementasi Programable Logic Control Dan Wonderware Intouch Untuk Otomasi Smart Home - Sarifuddin Sarifuddin; Nur Yanti (Jurnal Teknologi Terpadu, 2014)
Abstract The development of technology in the field of automation today, allows humans to create an automatic control system that is monitored in order to provide all the comfort, safety, security and energy savings in the home. it requires a control system programmed through a computer that controls almost all of the equipments in home. With smart home control center using a PLC (Programmable Logic Control) Omron CPM1A 30 CDR. This has a smart home control lighting system using LEDs for lighting inside and outside home, security systems function in the accident of theft by using magnetic door sensor and PIR with alarm indication, then to the security system of a gas leak using MQ6 used in the accident of a gas leak especially LPG gas with shutdown output system that has function for the security in home, Smart home automation system is only using a sensor LDR when dark / night light automatically turns on terrace home and the smart socket to control appliances in the smart home using a miniature fan and TV. This control can be done with dual systems that by manual system using deep switch and the remote system using the SCADA HMI (Human Machine Interface). HMI here is using Wonderware Intouch software that has functions as a liaison between the human (operator) with a smart home appliance via a computer or smart Phone. By using smart home system is capable of providing many benefits and advantages to the home owner in the future in terms of energy, cost and effort.Keywords : Smart Home, Programable Logic Control, Wonderware Intouch AbstrakPerkembangan teknologi dalam bidang otomasi saat ini, memungkinkan manusia untuk menciptakan suatu sistem kontrol otomatis yang termonitor guna memberikan segala kenyamanan, keselamatan, keamanan dan penghematan energi didalam suatu rumah. Untuk itu dibutuhkan sistem kontrol yang terprogram melalui sebuah komputer yang mengendalikan hampir semua perlengkapan dan perlatan rumah. Dengan Pusat pengontrolan smart home menggunakan PLC (Programmable Logic Control) Omron CPM1A 30 CDR. Dalam smart home ini terdapat pengontrolan sistem lighting menggunakan LED untuk penerangan di dalam dan luar rumah, sistem keamanan berfungsi apabila terjadi kemalingan dengan mengunakan sensor magnetic door dan PIR dengan indikasi alarm, kemudian untuk sistem keamanan dari kebocoran gas menggunakan MQ6 yang digunakan jika terjadi kebocoran gas khususnya gas LPG dengan output shutdown system yang berfungsi untuk mengamankan suatu rumah, sistem otomasi dalam smart home ini hanya mengunakan sensor LDR ketika gelap/malam hari lampu teras rumah menyala secara otomatis dan smart socket untuk kontrol peralatan rumah dalam smart home ini mengunakan miniature kipas dan TV. Pengontrolan ini dapat dilakukan dengan dual sistem yaitu dengan sistem manual mengunakan deep switch dan sistem remote dengan mengunakan SCADA HMI (Human Machine Interface). HMI disini mengunakan software Wonderware Intouch yang berfungsi sebagai penghubung antara manusia (Operator) dengan alat smart home melalui  sebuah computer atau smart Phone. Dengan mengunakan sistem smart home ini mampu memberikan banyak manfaat dan keuntungan kepada pemilik rumah kedepanya dari segi energi, biaya dan tenaga.Kata kunci : Smart Home, Programable Logic Control, Wonderware Intouch